Delay Reduction On Gpon By Modifying Bi-partition Dynamic Bandwidth Allocation Method - Kurnia Triningsih; Erna Sri Sugesti; Sofia Naning H (eProceedings of Engineering, 2017)
The majority of the optical fiber access network is currently dominated by Gigabit Passive Optical Network (GPON) technology, which is able to provide various services on the network. Dynamic Bandwidth Allocation (DBA) is used for control the upstream bandwidth on GPON. This DBA method alocates an unused timeslot for another Optical Network Termination (ONT) with a particular priority and set the maximum permitted frame length to be transmitted in order to get equal opportunities in data delivery. We proposed Multi partition DBA that divides time cycle into four groups. Simulation was conducted to compare the performance of Multi Partition DBA with two different schemes. This method improved the total delay performance since the number of partitions resolved the idle period and made DBA computation time more effectively.Â